Global Health Governance Or Global Governance For Health? Navigating The Path For Pandemic Preparedness - AbdelMotaal, kadria (AUC Knowledge Fountain, 2026)
Abstract The COVID-19 pandemic constituted a systemic stress test for global health governance, exposing structural and institutional weaknesses in national and international response systems. Although health system financing and income levels influenced baseline capacity, this dissertation demonstrates that governance performance was a decisive determinant of pandemic outcomes, shaping intervention timing, vaccine equity, and preventable mortality. Drawing on governance theory, empirical analysis, and policy-oriented legal evaluation, this research examines whether pandemic preparedness can be achieved through strengthening Global Health Governance (GHG) alone, or whether a broader paradigm of Global Governance for Health (GGFH) is required. GGFH reconceptualizes preparedness as embedded within global rule-making systems beyond the health sector, including trade and intellectual property regimes, international financing structures, geo-political dynamics, supply chains, and enforceable accountability mechanisms. Methodologically, the dissertation proceeds through five integrated stages. First, a document-based theoretical analysis of governance models, including multilevel governance, network governance, meta-governance, and good governance, develops conceptual criteria for evaluating governance performance and provides the theoretical foundation for the Global Governance for Health framework. Second, a mixed-methods empirical study integrates quantitative cross-national analysis with qualitative synthesis. The quantitative component combines data from the Oxford COVID-19 Government Response Tracker and the World Bank’s Worldwide Governance Indicators to assess the association between governance performance, intervention timing, mortality rates, and vaccine coverage disparities. The qualitative component undertakes a structured evaluative synthesis of governance performance across the same analytical dimensions examined quantitatively, enabling triangulation of findings and strengthening the robustness of the study’s conclusions. Third, a scoping review synthesizes 52 peer-reviewed and policy sources (2019–2024) to identify recurrent governance deficits related to enforcement, equity, institutional capacity, and coordination, generating an empirical foundation for subsequent treaty evaluation. Fourth, a qualitative gap analysis assesses the 2025 WHO Pandemic Agreement against these empirically derived challenges. Fifth, the dissertation develops a Global Governance for Health framework, validated through a three-round Delphi study involving thirty-one experts across global health, law, finance, and policy domains. Empirical findings demonstrate that governance effectiveness, operationalized through a composite indicator of Government Effectiveness and Regulatory Quality, was a statistically significant predictor of early intervention, reduced mortality, and broader vaccine coverage, independent of income level. The scoping review and treaty analyses reveal persistent structural deficits in enforceability, technology transfer, sustainable financing, and inclusive representation, particularly affecting low- and middle-income countries, which remain only partially addressed by the WHO Pandemic Agreement. The Delphi study validated a framework structured across seven interdependent governance domains, achieving expert consensus on the centrality of legal preparedness, equitable financing, institutional accountability, strengthened WHO coordination, and meaningful LMIC representation. Interdependence analysis confirms that legal and financial infrastructures function as foundational enablers of downstream equity and implementation outcomes. This dissertation makes three principal contributions. Empirically, it establishes governance performance as an independent and quantifiable determinant of pandemic outcomes. Analytically, it provides one of the earliest systematic mappings between treaty provisions and empirically identified governance gaps. Conceptually, it advances a validated, implementation-oriented Global Governance for Health framework that complements the WHO Pandemic Agreement by strengthening its operationalization and addressing unresolved institutional weaknesses. The findings demonstrate that effective and equitable pandemic preparedness cannot be achieved through health-sector–centric governance alone. Rather, it requires an integrated Global Governance for Health approach that embeds health within the broader architecture of global decision-making, supported by enforceable, coordinated, and accountable institutional arrangements.